Understanding literature - Robin Mayhead (Cambridge ; London Cambridge University Press, 1965)
In this book, originally published in 1965, Mr Mayhead gives an introduction to the reading and study of English literature. It is not an historical summary, but an attempt to say why literature is important, how it works, and how it can be approached.
Keywords: English literature -- History and criticism; English literature